Equitable Access to Antibiotics: A Core Element and Shared Global Responsibility for Pandemic Preparedness and Response. (2022) - Ren, Mengying; So, Anthony D.; Chandy, Sujith J.; Mpundu, Mirfin; Peralta, Arturo Quizhpe; Åkerfeldt, Kerstin; Sjöblom, Anna Karin; Cars, Otto
Abstract: Securing equitable antibiotic access as an essential component for health system resilience and pandemic preparedness requires a systems perspective. This article discusses key components that need to be coordinated and paired with adequate financing and resources to ensure antibiotic effectiveness as a global public good, which should be central while discussing a new global agreement.